A Posthuman Perspective on Entrepreneurial Competence Development for Vocational College Students - Hu, Wanqiu; Chookhampaeng, Chowwalit; Chano, Jiraporn (Journal of Posthumanism, 2025)
Traditional entrepreneurship education often privileges human-centered agency and cognitive mastery, overlooking the entanglements of digital technologies, environments, and sociotechnical systems. The objective of this research is to investigate a posthuman perspective on entrepreneurial competence development for vocational college students. Conducted at a vocational college, the study implemented an eight-week extracurricular entrepreneurship course designed in accordance with posthumanist educational principles. The research involved 30 student participants and 5 expert consultants, using a mixed-methods approach that included pre- and post-intervention tests, surveys, interviews, reflective journals, and artifact analysis. Quantitative data were analyzed using paired samples t-tests, while qualitative data underwent thematic coding guided by concepts of relationality and intra-action. Results indicated significant gains in students’ entrepreneurial knowledge, practical skills, and attitudes, attributed not to isolated learning but to hybrid engagements with peers, mentors, technologies, and learning environments. These findings suggest that posthumanist pedagogies foster adaptive, co-creative, and context-sensitive entrepreneurial capacities. The study recommends further integration of hybrid experiential learning environments and proposes expanded research across varied cultural contexts to evaluate the broader applicability of posthuman educational models.